Panas Dingin Kehidupan Keberagaman Kawasan Asia Selatan (Dari Masa Dinasti Mughal Hingga Kontemporer) - Fikri Surya Pratama; Jupri Jupri (IAIN Bengkulu, 2023)
The South Asian region itself is an area that has a history of people who aren’t free from conflict. This happens because disorganized of the diversity of society consisting of various races and religions. Islam which had triumphed in this region from the 8th century to the 18th century AD was enough to color the cultural life of the people of South Asia. This article aims to explain how the history and development of Muslim societies in South Asian countries from the Mughal Dynasty to the contemporary. The method used in this research is the historical research method, with the steps: 1) Heuristics or collection of sources collected through library research by searching for books, previous research journals and popular news sites that update on the situation of Muslims in the South Asian region; 2) Source Criticism, namely the activity of selecting sources based on their strengths; 3) Interpretation or research analysis stage; 4) historiography or the last stage of this research in the form of historical scientific writings. The results of the study show that countries such as India and Sri Lanka have quite complicated racial issues in their religious communities. Bangladesh, Afghanistan and Pakistan, which are Muslim-majority countries, are confused with their internal and political problems with India. The Maldives is able to become a good Muslim model country in the South Asian region, as well as good tolerance for Bhutan and Nepal which have Muslim minorities.Kawasan Asia Selatan sendiri merupakan wilayah yang memiliki sejarah masyarakat yang tak lepas dari konflik. Hal ini terjadi dikarenakan tidak terorganisir keberagaman masyarakat yang terdiri dari berbagai macam ras dan agama. Islam yang sempat berjaya di kawasan ini sejak abad ke-8 hingga abad ke-18 M cukup mewarnai corak kebudayaan kehidupan masyarakat Asia Selatan. Artikel ini bertujuan untuk menjelaskan bagaimana sejarah dan perkembangan masyarakat muslim di negara-negara Asia Selatan dari masa Dinasti Mughal hingga kontemporer. Metode yang dipakai dalam penelitian ini adalah metode penelitian sejarah, dengan langkahnya: 1) Heuristik atau pengumpulan sumber yang dikumpulkan lewat studi pustaka dengan mencari buku-buku, jurnal penelitian terdahulu dan situs berita populer yang update mengenai situasi ummat Muslim di kawasan Asia Selatan; 2) Kritik Sumber yakni kegiatan menyeleksi sumber-sumber berdasarkan kekuatannya; 3) Interpretasi atau tahap analisis penelitian; 4) historiografi atau tahap terakhir penelitian ini berupa karya tulis ilmiah sejarah. Hasil penelitian menujukkan bahwasannya negara-negara seperti India dan Sri Lanka memiliki persoalan rasial yang cukup rumit dalam ummat beragamanya. Bangladesh, Afganistan dan Pakistan tang menjadi negara mayoritas muslim dipusingkan dengan persoalan internal negara dan politik mereka dengan India. Maladewa mampu menjadi negara percontohan muslim yang baik di kawasan Asia Selatan, serta toleransi yang bagus juga pada Bhutan dan Nepal yang memiliki kelompok minoritas muslim.